고관절 주위 절골술 - 조윤제; Yoon Je Cho; 곽상준; Sang Joon Kwak; 김환진; Hwan Jin Kim; 이상훈; Sang Hoon Lee (Hip & pelvis, 2012)
인공 고관절로의 치환없이 본인의 고관절을 보존하며, 비구 또는 대퇴 근위부의 구조적 이상을 교정하는 고관절 주변 절골술은, 심각한 퇴행성 변화가 없는 젊은 환자에게 인공 고관절 수술 보다 더욱 이상적인 술식으로 받아들여지고 있다. 지난 20 여 년 동안 다양한 고관절 진환에 대한 다양한 종류의 비구 주변 또는 대퇴 근위부 절골 수술들이 소개되어 왔으며, 이러한 술기에 대한 다양한 결과들이 보고되어 왔다. 본 연구에서는 이러한 다양한 종류의 고관절 주변 절골술과 이들의 적용 질환 그리고 그 결과에 대하여 논하고자 한다. Hip joint preserving osteotomy surgery is the treatment of choice for young patients with early symptomatic structural abnormalities of the acetabulum and proximal femur. This is true even in the absence of severe secondary degenerative changes. These disorders can include hip instability from classic developmental dysplasia, posttraumatic acetabular dysplasia, hip impingement from retrotorsional acetabular deformities, or, rarely, post-traumatic problems. During the past 20 years, various techniques of acetabular and proximal femoral reorientation have evolved, making the procedure reliable, reproducible, and durable. In this report, the current indications and results of acetabular and proximal femoral osteotomies in patients with symptomatic acetabular structural problems will be discussed.